Flea Market in Minangkabau Community: The Expression of Social and Cultural - Damsar Damsar; Indrayani Indrayani; Ria Ariany; Surya Suryadi (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2023)
The flea market constituted a specific phenomenon in the context of market formation. Some social, cultural, and structural backgrounds trigger the formation of a flea market. This research aimed to uncover the processes of forming the flea market in Bukitinggi as a part of the Minangkabau community, in West Sumatra, Indonesia. By applying the qualitative method, data were collected from observations and in-depth interviews with informants from the Bukittinggi flea market. The 14 informants participating in this research were the flea market’s managers, sellers, and buyers. The thematic observations were carried out regularly to capture the real conditions and the discussions among the community members. The data analysis and triangulation refer to Miles and Huberman’s model. The findings confirm Aspers’ approach to market formation. The flea market was formed through three simultaneous processes: spontaneous, autonomous, and state-governed market creation. The stages of the flea market formation were orientation, contraction, and cohesion involving state actors, sellers, and buyers. The cultural barriers in the orientation process were removed during the contraction stage through various social constructions and the state’s involvement in market relocation. The cohesion was formed by upholding the community’s cultural traditions.